2008
DOI: 10.1093/hmg/ddn227
|View full text |Cite
|
Sign up to set email alerts
|

A high-density association screen of 155 ion transport genes for involvement with common migraine

Abstract: The clinical overlap between monogenic Familial Hemiplegic Migraine (FHM) and common migraine subtypes, and the fact that all three FHM genes are involved in the transport of ions, suggest that ion transport genes may underlie susceptibility to common forms of migraine. To test this leading hypothesis, we examined common variation in 155 ion transport genes using 5257 single nucleotide polymorphisms (SNPs) in a Finnish sample of 841 unrelated migraine with aura cases and 884 unrelated non-migraine controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 51 publications
(58 reference statements)
4
66
1
1
Order By: Relevance
“…Among the 38 migraine loci only two harbor known ion channels (KCNK5 23 and TRPM8 24 ), while three additional loci (SLC24A3 26 , ITPK1 27 , and GJA1 28 ) can be linked to ion homeostasis. This further supports the findings of previous studies that in common forms of migraine, ion channel dysfunction is not the major pathophysiological mechanism 20 . However, more generally, genes involved in ion homeostasis could be a component of the genetic susceptibility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the 38 migraine loci only two harbor known ion channels (KCNK5 23 and TRPM8 24 ), while three additional loci (SLC24A3 26 , ITPK1 27 , and GJA1 28 ) can be linked to ion homeostasis. This further supports the findings of previous studies that in common forms of migraine, ion channel dysfunction is not the major pathophysiological mechanism 20 . However, more generally, genes involved in ion homeostasis could be a component of the genetic susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…In familial hemiplegic migraine (FHM), a rare Mendelian form of the disease, three ion transport-related genes (CACNA1A, ATP1A2 and SCN1A) have been implicated [17][18][19] . These findings suggest that mechanisms that regulate neuronal ion homeostasis might also be involved in MO and MA, however, no genes related to ion transport have yet been identified for these more prevalent forms of migraine 20 .…”
mentioning
confidence: 92%
“…However, a recent extensive screen of a European population concluded that common variants in ion transport genes do not play a major role in susceptibility to common migraine. 28 The search for genes for common migraine continues.…”
Section: Migraine Geneticsmentioning
confidence: 99%
“…Like other complex genetic traits, finding responsible genes are much more difficult (de Vries et al, 2006). Despite these problems and absence of any evidence of association between genes encoding the ion channels and common migraine in previous studies (Nyholt et al, 2008), it has been reported recently that there is a strong genetic link to common forms of migraine (Lafrenière et al, 2010). Using a candidate gene approach and functional analysis, researchers have identified a mutation, F139wfsX24, in the gene encoding the two-pore domain potassium channel TRESK (TWIK-related spinal cord potassium channel) KCNK18 in the patients with migraine with aura.…”
Section: Common Migrainementioning
confidence: 97%